Assessment of Experimental Artifacts in Evaporation Tests on Isolated, Suspended Droplets - Asrardel, Mohamad; Poonawala, Taha; Muelas, Álvaro; Ballester, Javier (Jornada de Jóvenes Investigadores del I3A, 2023)
The suspended droplet framework is commonly used to study liquid fuel evaporation and combustion. However, measurements at this facility can be affected by artifacts. This study examines their impact on butanol droplet evaporation. Thermal radiation and fiber conduction effects are specifically addressed. Results show that heat conduction through the fiber can significantly affect droplet evaporation, even causing internal bubbling in some cases.